Membangun Pemahaman Bacaan Mahasiswa melalui Aktivitas Pascabaca - Indah Pujiastuti; Vismaia S. Damaianti; Syihabuddin Syihabuddin (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
Activity after reading (post-reading) is the stage where a reader responds to what he has read. At this stage, it is hoped that there will be changes from readers, changes in mindset, understanding, and increasing knowledge. This study describes the implementation of activities after reading carried out by students independently and structured. This research is a descriptive survey. Data were obtained from questionnaires distributed to 246 students and 11 lecturers of the Indonesian Language and Literature Education Departments, Raja Ali Haji Maritime University. The findings are, first, the majority of students read fiction when reading independently. After reading, students carry out various activities such as recording quotes, summarizing readings, recording difficult vocabulary, and discussing. Second, when reading in a structured way, students read a lot of non-fiction, such as reference books, scientific articles, research reports, handouts. Activities carried out after structured reading are writing activities such as summarizing, compiling presentation materials, writing reports, and writing reviews. However, students' have obstacles when completing activities after reading, such as difficulty in concluding readings, understanding sentences, and reading vocabulary there that the expected results after reading are not optimal. These obstacles cause students to only rewrite (copy-paste) readings. Students have not yet reached the stage of how critical reading and building their mindset.